Ring test assessment of the mKir2.1 growth based assay in Saccharomyces cerevisiae using parametric models and model-free fits - Hasenbrink, Guido; Kolacna, Lucie; Ludwig, Jost; Sychrova, Hana; Kschischo, Maik; Lichtenberg-Fraté, Hella (Applied microbiology and biotechnology, 2007)
Inward rectifying K+ (Kir) channels are a subfamily of the potassium channel superfamily. They mediate potassium influx into the cells, a process responding to the polarization state, a variety of intracellular messengers and specific auxiliary proteins, thereby they are involved in important physiological processes such as the pacemaker activity in the heart, insulin release, and potassium uptake in glial cells. The Saccharomyces cerevisiae mKir2.1 in vitro assay was subjected to a ring test assessment. Compound-associated mKir2.1 modulating effects were detected by growth determination of functionally complemented S. cerevisiae cells in a 96-well format within 15 h. Dose-response diagrams and EC50 value calculations were determined by parametric model and model-free fits using cubic spline interpolation. These characteristics were evaluated by statistical methods to determine reproducibility among working groups. Nonparametric bootstrap simulations of the variability of the data revealed that EC50 values of the mKir2.1 indicator strain were well-matched (81-92 microM), enabling unambiguous quantitative statements about inhibitory effects and no significant influence of the different laboratory conditions. Limitations of the assay include compounds/samples that are either insoluble under the conditions of the test or strongly cytotoxic to yeast. Thus, the described test is a sensitive and reliable tool that can be used in different laboratories and is applicable in drug discovery and development as simple and reliable prescreening procedure.